Fungicides and Application Timing for Control of Early Leafspot, Southern Blight, and Sclerotinia Blight of Peanut - W. James Grichar; Jason E. Woodward (International Journal of Agronomy)
Field studies were conducted in 2013 and 2014 in south Texas near Yoakum and from 2008 to 2011 in central Texas near Stephenville to evaluate various fungicides for foliar and soilborne disease control as well as peanut yield response under irrigation. Control of Sclerotinia blight caused by Sclerotinia minor Jagger with penthiopyrad at 1.78 L/ha was comparable to fluazinam or boscalid; however, the 1.2 L/ha dose of penthiopyrad did not provide consistent control. Peanut yield was reduced with the lower penthiopyrad dose when compared with boscalid, fluazinam, or the high dose of penthiopyrad. Control of early leaf spot, caused by Cercospora arachidicola S. Hori or southern blight, caused by Sclerotium rolfsii Sacc., with penthiopyrad in a systems approach was comparable with propiconazole, prothioconazole, or pyraclostrobin systems and resulted in disease control that was higher than the nontreated control. Peanut yield was also comparable with the penthiopyrad, propiconazole, prothioconazole, or pyraclostrobin systems and reflects the ability of the newer fungicides to control multiple diseases found in Texas peanut production.